PEMODELAN KUALITAS PENDIDIKAN TERHADAP TINGKAT PENGANGGURAN TERBUKA DI JAWA BARAT MENGGUNAKAN GEOGRAPHICALLY WEIGHTED REGRESSION (GWR) - Intan Amelia Haryanto; Saputri Dyah Pratiwi; Putri Amelia Divaio; Gangga Anuraga (Seminar Nasional Hasil Riset dan Pengabdian, 2024)
The open unemployment rate in Indonesia ranked the second highest in Southeast Asia in 2022,with a rate of 5.86 percent, or approximately 8.47 million people. This study aims to analyze theimpact of education quality on the open unemployment rate in West Java Province using theGeographically Weighted Regression (GWR) method. The dependent variable in this study is theopen unemployment rate (TPT), while the independent variables include expected years ofschooling, labor force participation rate, number of poor people, literacy rate of the populationaged 15 and over, net enrollment rate, mobile phone usage by students aged 5-24 years over thepast three months, and average years of schooling. The data used are secondary data from theCentral Bureau of Statistics (BPS) and the West Java Provincial Education Statistics for 2022,covering 27 regencies/cities. The analysis results show that the GWR model provides betterestimates compared to the OLS model, with a higher R-Square value and a lower AIC. The factorsthat significantly affect the TPT in each regency/city in West Java Province are the average yearsof schooling and the net enrollment rate. This research is expected to contribute to theformulation of effective education policies to reduce the open unemployment rate in West JavaProvince.Keywords: Quality of Education, Open Unemployment Rate (TPT), Geographically WeightedRegression (GWR), Average Years of Schooling, Net Enrollment Rate (NER).